1989
DOI: 10.1161/01.str.20.8.1095
|View full text |Cite
|
Sign up to set email alerts
|

Occlusion of the middle cerebral artery due to cysticercotic angiitis.

Abstract: Three patients with cysticercosis developed a cerebral infarct secondary to the occlusion of the middle cerebral artery or its major branches. Histopathologic examination revealed a large subarachnoid cysticercus surrounding the occluded arteries in two patients and diffuse thickening of the leptomeninges in one. Blood vessels around the parasite showed inflammatory changes that caused either occlusive endarteritis or thrombosis due to disruption of the endothelium. Cysticercosis should be considered as a caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0
2

Year Published

1992
1992
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 11 publications
1
22
0
2
Order By: Relevance
“…Cerebrovascular complications, which are the result of multiple mechanisms, including luminal narrowing due to subintimal cushions, vasospasm due to arteritis in midsized and small perforating vessels of the brain, and fresh thrombi (29). The spectrum of vascular complications includes either lacunar infarction or large-vessel disease, progressive midbrain syndrome, transient ischemic attacks, and brain hemorrhage (29,30).…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Cerebrovascular complications, which are the result of multiple mechanisms, including luminal narrowing due to subintimal cushions, vasospasm due to arteritis in midsized and small perforating vessels of the brain, and fresh thrombi (29). The spectrum of vascular complications includes either lacunar infarction or large-vessel disease, progressive midbrain syndrome, transient ischemic attacks, and brain hemorrhage (29,30).…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Some patients, however, present with rapid development of focal signs due to the occurrence of a cerebrovascular event. 13,52 Other patients present with increased intracranial pressure and dementia signs. Hydrocephalus, related to cysticercal arachnoiditis, granular ependymitis, or ventricular cysts, is the most common cause of this syndrome.…”
mentioning
confidence: 99%
“…8 Angiographic studies have rarely shown arterial thrombosis in cerebral cysticercosis. 349 - 13 In those patients with cerebral cysticercosis and stroke, vascular events have been related to thrombosis of the superficial cortical vessels owing to chronic meningitis, 1415 to arteritis induced by the presence of adjacent cysts, 1215 - 18 to fusiform aneurysms produced by weakening of the wall of the vessels, 12 and to occlusion of small perforating vessels affected by endarteritis.…”
mentioning
confidence: 99%